Mass mediations : new approaches to popular culture in the Middle East and beyond - Armbrust, Walter (Berkeley : University of California Press, 2000)
Offering a stimulating diversity of perspectives, this collection examines how popular culture through mass media defines the scale and character of social interaction in the Middle East. The contributors approach popular culture broadly, with an interest in how it creates new scales of communication and new dimensions of identity that affect economics, politics, aesthetics, and performance.
Introduction: Anxieties of Scale / Walter Armbrust -- Public Culture in Arab Detroit: Creating Arab/American Identities in a Transnational Domain / Andrew Shryock -- The 6/8 Beat Goes On: Persian Popular Music from Bazm-e Qajariyyeh to Beverly Hills Garden Parties / Anthony Shay -- Sa'ida Sultan/Danna International: Transgender Pop and the Polysemiotics of Sex, Nation, and Ethnicity on the Israeli-Egyptian Border / Ted Swedenburg -- Playing It Both Ways: Local Egyptian Performers between Regional Identity and International Markets / Katherine E. Zirbel -- Joujouka/Jajouka/Zahjoukah: Moroccan Music and Euro-American Imagination / Philip Schuyler -- Nasser 56/Cairo 96: Reimaging Egypt's Lost Community / Joel Gordon -- Consuming Damascus: Public Culture and the Construction of Social Identity / Christa Salamandra -- The Hairbrush and the Dagger: Mediating Modernity in Lahore / Richard McGill Murphy -- "Beloved Istanbul": Realism and the Transnational Imaginary in Turkish Popular Culture / Martin Stokes -- Badi'a Masabni, Artiste and Modernist: The Egyptian Print Media's Carnival of National Identity / Roberta L. Dougherty -- American Ambassador in Technicolor and Cinemascope: Hollywood and Revolution on the Nile / Robert Vitalis -- The Golden Age before the Golden Age: Commercial Egyptian Cinema before the 1960s / Walter Armbrust.
Includes bibliographical references (pages 329-353) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Mass media -- Middle East; Popular culture -- Middle East; SOCIAL SCIENCE -- Media Studies; Mass media; Popular culture; Middle East; Massenkultur; Kongress; Naher Osten; Massamedia; Populaire cultuur; Electronic book